The psychological impact of overactive bladder: A systematic review. (January 2016) - Kinsey, Debbie; Pretorius, Sara; Glover, Lesley; Alexander, Tim
This review aimed to provide an overview of the current research on the psychological impact of overactive bladder. A systematic search yielded 32 papers. It was found that people with overactive bladder tended to have greater levels of depression, anxiety and embarrassment/shame; difficulties with social life; impact on sleep and sexual relationships; and a lower quality of life than people without overactive bladder. A psychological impact on family members was also found. Psychological health should be considered an important aspect of managing overactive bladder and further research is required to determine how best to provide psychological care and support in this area.